2018
DOI: 10.15578/bawal.10.2.2018.95-104
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN TONGKOL ABU-ABU, Thunnus tonggol (Bleeker, 1851) DI PERAIRAN LAUT JAWA

Abstract: Tongkol abu-abu atau longtail tuna (Thunnus tonggol) salah satu jenis ikan tuna neritik sebagai target penangkapan armada pukat cincin, jaring isang, dan pancing di Laut Jawa. Penelitian ini bertujuan untuk mengetahui parameter pertumbuhan, umur dan mortalitas ikan tongkol abu-abu untuk penyusunan strategi pengelolaannya. Pengumpulan data frekuensi panjang dan bobot ikan dilakukan di Pelabuhan Perikanan Nusantara (PPN) Pekalongan pada Januari – Nopember 2014. Hasil penelitian menunjukkan hubungan panjang-bobot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…Laut Jawa (WPPNRI 712) merupakan perairan territorial, kegiatan penangkapan sebagian besar dilakukan di perairan utara Jawa, dengan potensi ikan pelagis yang cukup besar (Suman et al 2017). Pada tahun 2014 produksi perikanan tangkap di Laut Jawa terbesar di seluruh Indonesia yaitu (17,91% dari total produksi Indonesia) 6.037.654 ton (Restiangsih & Hidayat 2018).…”
Section: Pendahuluanunclassified
“…Laut Jawa (WPPNRI 712) merupakan perairan territorial, kegiatan penangkapan sebagian besar dilakukan di perairan utara Jawa, dengan potensi ikan pelagis yang cukup besar (Suman et al 2017). Pada tahun 2014 produksi perikanan tangkap di Laut Jawa terbesar di seluruh Indonesia yaitu (17,91% dari total produksi Indonesia) 6.037.654 ton (Restiangsih & Hidayat 2018).…”
Section: Pendahuluanunclassified
“…In one of the T. tonggol study in Java Sea, it is mentioned that the conditions of this species in the areas are listed as fully exploited (Restianingsih and Hidayat 2018), which then rise a sustainable fisheries issue because Indonesia and other countries such as Thailand, Malaysia, and Iran are the countries that have a high contribution on the T. tonggol fisheries in the world (Griffiths et al 2010;Abdussamad et al 2012;Darvishi et al 2018). Another study conducted in Southwest Aceh indicated that the condition of T. tonggol population in that area indicated a low vulnerability status and high productivity rate, which signifies that the Longtail Tuna population in Southwest Aceh is still in a good level of resource sustainability category (Rahma et al 2019).…”
Section: Genetic Diversity and Genetic Structurementioning
confidence: 99%
“…Longtail Tuna usually found around Indo-Pacific waters (Sharma et al 2012;Kunal et al 2014;Froese and Pauly 2019). In Indonesia, T. tonggol species is easy to find within the area of Java Sea, including in the Fisheries Management Area-712 (FMA-712) with a total area of 320.000 km 2 (Restianingsih and Hidayat 2018); Kep-Men KKP 2016). In their report, it is also mentioned that there is indication of full exploitation of Longtail Tuna population within Java Sea (Restianingsih and Hidayat 2018), which will impact the sustainable fisheries of this species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations